DEVELOPMENT OF SELF-REFLECTION INSTRUMENTS OF RIAS LEARNING MODEL IN STUDENTS OF ENVIRONMENTAL EDUCATION COURSE - Ahmad Muhlisin; Sri Sarwanti; Gentur Jalunggono; Arnanda Yusliwidaka; Sukron Mazid (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
It is necessary to measure student spiritual and social attitudes to find out their attitude development in students ofenvironmental education course. The research aims to develop instruments utilized in measuring student spiritual and social attitudes in RIAS (Reading, Identification, Analysis, and Self-reflection) learning model implementation. Theresearch procedures consist of 1) needs analysis and literature study; 2) instrument design; 3) instrument development; 4) expert assessment; 5) instrument revision; and 6) instrument dissemination. The research instruments utilized include content validity sheets and construct validity instruments with assessment scale score of 1-4 consisting of (1) not feasible; (2) less feasible; (3) feasible; and (4) very feasible. The research results indicate that 1) the instruments ofspiritual and social attitudes measurement in the RIAS learning model implementation are feasible to be utilized in measuring student spiritual and social attitudes. It is indicated by validation score of 3.8 and 2) further research and development includes portfolio development to measure spiritual and social attitudes. The research implications become a practical reference for teachers and lecturers in measuring spiritual and social attitudes in learning.